PENGARUH CITRA MEREK DAN KEPERCAYAAN MEREK TERHADAP KEPUTUSAN PEMBELIAN MASKER MEREK SENSI OLEH PELANGGAN DI KOTA BANJARMASIN - Annisa Maulita; Taharuddin; Hairudinor (Business Administration, FISIP ULM, 2023)
This study aims to determine and test partially and simultaneously the effect of brand image and trust on customer decisions to purchase Sensi brand masks in Banjarmasin City. This study uses a quantitative approach. The sample in this study were brand mask customers with a total of 100 respondents with a sampling technique using accidental sampling. Data processing was carried out using multiple linear regression analysis, partial test (t test), and simultaneous test (F test). The results showed that brand image and trust influenced the purchasing decisions of Sensi brand masks by customers in Banjarmasin City. In addition, simultaneously brand image and brand trust also affect the buying decisions of Sensi brand masks by customers in Banjarmasin City.